A Nonlethal Method to Examine Non-Apis Bees for Mark-Capture Research. Issue 3 (4th June 2018) - Boyle, Natalie K; Tripodi, Amber D; Machtley, Scott A; Strange, James P; Pitts-Singer, Theresa L; Hagler, James R
Abstract: Studies of bee movement and activities across a landscape are important for developing an understanding of their behavior and their ability to withstand environmental stress. Recent research has shown that proteins, such as egg albumin, are effective for mass-marking bees. However, current protein mass-marking techniques require sacrificing individual bees during the data collection process. A nonlethal sampling method for protein mark-capture research is sorely needed, particularly for vulnerable, sensitive, or economically valuable species. This study describes a nonlethal sampling method, in which three non- Apis bee species ( Bombus bifarius Cresson [Hymenoptera: Apidae], Osmia lignaria Say [Hymenoptera: Megachilidae], and Megachile rotundata Fabricius [Hymenoptera: Megachilidae] ) were tested for a unique protein marker by immersing them momentarily in saline buffer and releasing them. Results showed that an egg albumin-specific enzyme-linked immunosorbent assay was 100% effective at detecting the protein on bees that were sampled nonlethally. Furthermore, this sampling method did not have an impact on bee survivorship, suggesting that immersing bees in buffer is a reliable and valid surrogate to traditional, destructive sampling methods for mark-capture bee studies.